As zonas de processamento de exportação como instrumento de desenvolvimento e redução das desigualdades regionais - Vieira, Edmar Eduardo de Moura (2013)
The existence of inequalities among the Brazilian regions is an indeed fact along the country s history. Before this reality the constitutional legislator inserted into the Federal Constitution of 1988, as a purpose of the Federative Republic of Brazil, the reduction of regional inequalities. The development has also been included as a purpose from the State, because there is an straight relation with the reduction of regional inequalities. In both situations is searched the improvement of people s living conditions. . In pursuit of this achievement, the State must implement public policy, and, for this to happen, it needs the ingress of income inside of the public coffers and support of economic agents, therefore the importance of constitucionalization of the economic policy. The 1988 s Constitution adopted a rational capitalism regime consentaneous with current legal and social conceptions, that s why it enabled the State s intervention into economy to correct the so-called market failures or to make the established objectives fulfilled. About this last one, the intervention may happen by induction through the adoption of regulatory Standards of incentive or disincentive of economic activity. Among the possible inductive ways there are the tax assessments that aim to stimulate the economic agents behavior in view of finding that the development doesn t occur with the same intensity in all of the country s regions. Inside this context there are the Export Processing Zones (EPZs) which are special areas with different customs regime by the granting of benefits to the companies that are installed there. The EPZs have been used, by several countries, in order to develop certain regions, and economic indicators show that they promoted economic and social changes in the places where they are installed, especially because, by attracting companies, they provide job creation, industrialization and increased exports. In Brazil, they can contribute decisively to overcome major obstacles or decrease the attraction of economic agents and economic development of the country. In the case of an instrument known to be effective to achieve the goals established by the Constitution, it is duty of the Executive to push for the law that governs this customs regime is effectively applied. If the Executive doesn t fulfill this duty, incurs into unjustifiable omission, correction likely by the Judiciary, whose mission is to prevent acts or omissions contrary to constitutional order